Energy, drinking water and health nexus in India and its effects on environment and economy - Vikrant P. Katekar (IWA Publishing, 2021)
This paper examines energy, drinking water and health nexus in India, and its consequences for the environment and economy. To establish this nexus, K-means cluster analysis and Davies–Bouldin validation index are employed to group 32 Indian states and union territories. The classification was performed based on 16 criteria, and the number of optimal clusters arrived at is 8. The nexus between energy, drinking water and health must be cautiously dealt with to ensure the social and economic growth of the nation. The criterion analysis of the states within these clusters indicates that states and union territories facing energy crises are usually deficient in safe drinking water services; consequently, people of those regions suffer from ill-health, which increases the economic burden on people through the loss of work productivity. With a deficient cash reserve, the communities are incapable of fulfilling the demand for energy and safe drinking water. However, while installing desalination plants to fulfil the need for safe drinking water, their environmental impact must be taken into account, as these systems have high energy consumption and significant environmental impact. HIGHLIGHTS This work examines energy, drinking water, and health nexus in India, and its effects on climate change.; States/union territories facing energy crises are usually deficient in safe drinking water services. Consequently, people suffer from ill-health, which increases their economic burden.; With a deficient cash reserve, the communities are incapable of fulfilling the demand for energy and safe drinking water;